Ultrasonic Waves for Algae Control in dam Lake: A Comprehensive Study of Mamloo Dam - Mehdi Vaezi; Amirhossein Javid; Seyed Mustafa Khezri; Mohsen Eslamizadeh (Entorno Geografico, 2025)
Dam reservoirs, which are crucial for managing river water quality (WQ), often face challenges from algal blooms caused by nutrient enrichment. This study investigates the use of ultrasonic waves (UWs) to control algal growth in Mamloo Dam. The objective is to assess the effectiveness of this technique and contribute to improved water management strategies.